Plant Resistance to Arthropods Molecular and Conventional Approaches - Smith, C. Michael (Springer Netherlands : Imprint: Springer, 2005)
Arthropod resistant crops reduce pesticide pollution, alleviate hunger and improve human nutrition. Plant Resistance to Arthropods - Molecular and Conventional Approaches synthesizes new information about the environmental advantages of plant resistance, transgenic resistance, the molecular bases of resistance, and the use of molecular markers to map resistance genes. Readers are presented in-depth descriptions of techniques to quantify resistance, factors affecting resistance expression, and the deployment of resistance genes. New information about gene-for-gene interactions between resistant plants and arthropod biotypes is discussed along with the recent examples of using arthropod resistant plants in integrated pest management systems.